Editorial - KUMAR, ARUNA T (Indian Farming, 2019)
Benefit: cost ratio of a farm depends upon the input cost, which is largely decided by the soil health, nutrient management and plant protection besides seeds etc. Efficient utilization of Soil health cards i.e., estimating the nutrient status of soil and then supplementing it with the required nutrients will not only reduce the expenditure on fertilizers but also keep the soil healthy. In India, 2.1% of the geographical area (about 6.73 million ha) of the country is salt affected; out of this 2.8 million ha are sodic and mainly occur in the Indo- Gangetic plains. The appropriate soil treatment can also bring the wastelands under farming, helping farmers earn more from degraded lands. The fragile soil health causes economic disaster to farmers, and those depending only upon crop sector can face difficult times.